Applying the triangulation approach in IT – business strategic alignment and sustainable competitive advantage - Almajali, Dmaithan Abdelkarim; Md Dahalin, Zulkhairi (IBIMA Publishing, 2011)
While researchers have encouraged more research on the causal chains between information technology investments and Business performance, the results of empirical studies have been inconclusive. This is partly due to the exclusion of IT-business strategic alignment. This study has examined the impact of IT-business strategic alignment antecedents in terms of leadership, structure and process, service quality, and value and belief on IT business strategic alignment in terms of alignment gap, followed by the impact of IT-business strategic alignment on sustainable competitive advantage. In order to explore the above research relationships, the study further utilizes the positivism paradigm by applying a mixed research method both quantitative and qualitative data. Such triangulation would help to provide more insight into the issues studied in this research. Particularly, this study has tested the research model by conducting 172 survey questionnaires with public shareholding firms in Jordan. After that, the study conducted several follow-up interviews in Jordan in order to further validate the research results. Thus, the results obtained from the structural equation modeling (SEM technique and supplementary qualitative analysis of the interviews offer a valuable insight into the research. However, the universal applicability of this research may be limited due to the fact that the results are based only on the cross-sectional data from the Jordanian public shareholding firms. Consequently, further research is needed with regards to several countries since this would help to advance understanding of the IT-business strategic alignment issue and the conditions and outcomes of achieving it in different contexts.